Pendampingan Ibu Hamil Untuk Penanganan Kekurangan Energi Kronik (KEK) Di Wilayah RT. 04 Kelurhana Ponorogo Kec. Lubuklinggau Utara 2 - Noviantika, Esti; Trismasari, Nova; Syahwitri, Dewi; Mayura, Mayura; Erlina, Erlina; Rossita, Taufianie (Jurnal Gotong Royong, 2026)
Chronic Energy Deficiency (CED) in pregnant women is one of the nutritional problems that has serious impacts on maternal health and fetal development. This condition commonly occurs due to limited nutritional knowledge and poor dietary habits. Assistance was provided to pregnant women in RT 04, Ponorogo Village, Lubuklinggau Utara II District for four weeks with the aim of increasing awareness, knowledge, and behavioral changes related to consuming balanced nutrition. The intervention included nutritional education, monitoring of eating patterns, and family involvement as supportive factors. The results showed positive changes in dietary habits, particularly for a participant named Rika, who previously consumed only two meals per day with minimal intake of protein and vegetables, but after the intervention increased to three meals per day with additional nutritious foods. Although the Mid-Upper Arm Circumference (MUAC) measurement did not show significant improvement in a short period, the change in dietary behavior indicates an important initial step toward preventing CED. Continued assistance is recommended to maintain these positive habits until delivery, considering that educational support and family involvement are proven to reduce the risk of CED in pregnant women.